Comparison of three fixation methods in paediatric metaphyseal-diaphysis junction fracture of the distal radius: a retrospective study in two centres - Jianyi, Jiang; Chaoyu, Liu; Lian, Meng; Ge, Meng; Hailong, Ma; Jun, Sun; Guoqiang, Jia (Frontiers in Pediatrics, 2023)
Background The distal radial metaphyseal-diaphysis junction fractures (DRMDJ) have various treatment methods and are easily lead to complications. This study aims to compare the anterograde elastic stable intramedullary nailing (ESIN-A), retrograde K-wire fixation (KW-R), and retrograde precision-shaping elastic intramedullary nailing (ESIN-RPS) for the treatment of pediatric DRMDJ fractures. Materials and methods A total of 113 patients with DRMDJ fractures (36 in the ESIN-A group, 52 in the KW-R group, and 25 in the ESIN-RPS group) from two centres were retrospectively analysed. Perioperative operation time, intraoperative bleeding, fluoroscopy times, alignment rate and angulation on radiography were compared among the three groups. Forearm rotation, healing, wrist function, and complications were compared at the last follow-up. Results The mean operation times of the three groups were as follows: KW-R (72 ± 13 min) > ESIN-A (65 ± 18 min) > ESIN-RPS (52 ± 11 min), with a significant difference (P < 0.01). The incision length and intraoperative blood loss of ESIN-A (1.8 ± 0.2 cm; 8.3 ± 3.7 ml) were significantly higher than ESIN-RPS (1.4 ± 0.8 cm; 5.5 ± 2.7 ml) (P < 0.05), respectively. The postoperative alignment rate on the anteroposterior (AP) and the lateral plane of ESIN-RPS (93.1 ± 4.4%; 95.01 ± 2.8%) was significantly greater than that of KW-R (82.1 ± 6.8%; 88.5 ± 4.5%) and ESIN-A (79.2 ± 5.2%; 83.2 ± 2.5%) (P < 0.01). The residual angulation of ESIN-RPS (3.3 ± 1.2°; 2.9 ± 0.8°) was significantly greater than that for ESIN-A (5.1 ± 1.7°; 4.9 ± 2.1°) and KW-R (6.6 ± 2.8°; 7.5 ± 1.6°) (P < 0.05). The excellent and good ratio of ESIN-RPS (95.8%) was significantly higher than that of ESIN-A (86.5%) and KW-R (86.1%) according to the Gartland-Werley standard. There was a significant difference in delayed union between the KW-R and ESIN-A (P < 0.05). Additionally, there were two cases of radial nerve injury in the ESIN-A group, one case of tendon rupture in the ESIN-RPS group, and one case of tendon rupture in the KW-R group. The ESIN-RPS group had significantly fewer complications than the KW-R group (P < 0.05). The ESIN-A group also had significantly fewer complications than the KW-R group (P < 0.05). Conclusion Compared with ESIN-A and KW-R, ESIN-RPS has the advantages of a shorter operation time, less intraoperative blood loss, less radiation, better alignment, and fewer complications. The ESIN-RPS was suggested as an optimal choice for paediatric DRMDJ fractures.